Energy flux measurements during magnetron sputter deposition processes - Thomann, A.-L.; Caillard, A.; Raza, M.; El Mokh, M.; Cormier, P.A.; Konstantinidis, S. (Surface & coatings technology, 2019)
The influence of energetic species on thin film growth mechanism is a long-term issue in the field of low-pressure plasma-based magnetron sputtering technology. Several species may contribute to the energy flux such a plasma ions, electrons and neutrals, film-forming species, photons, etc. Several research groups have designed probes capable of quantifying energy fluxes in these particular working conditions and experimental strategies to get a better insight on the relationship between the plasma working parameters, the energy flux, the film growth mechanism and the coating properties. In this paper we aim at showing how the thermopile-based probe developed at GREMI laboratory can contribute to this field thanks to its time resolved capability (~ms) and sensitivity (~mW/cm2). We show how such a probe can be used to identify and quantify energetic contributions such as gas conduction, chemical reactions on surfaces such as oxidation, but also radiations emitted from a (hot) sputter target during DC, pulsed-DC and High-power Impulse Magnetron Sputtering (HiPIMS) processes. Both non-reactive and reactive sputtering discharges are studied. Ultimately, we present data on the relationship between the phase composition and the energy deposited during the synthesis of two technologically important thin film materials, namely Titania and Zirconia. Through the reported examples, the advantage and limitations of energy flux measurements and the interest to couple the obtained data to those derived from conventional plasma diagnostics are discussed. The relative importance of various energetic contributions is investigated in a purpose to identify the key parameters driving the film properties. •Energy transferred to the film during deposition can be quantified.•The deposited energy at the substrate is the sum of elementary contributions.•Direct energy flux measurements allow investigating the sputter/deposition process.•IR radiations emitted by the heated target play a role on thin film final properties.•Energy deposited during deposition may hinder thermodynamic stabilization of phases.